12. EFEKTIVITAS KERJA SAMA PEMERINTAH LAOS DAN VIETNAM DALAM MENCEGAH DAN MEMBERANTAS HUMAN TRAFFICKING DI LAOS PERIODE 2011-2013 - Setyawati, Sari Widia; Utomo, Tri Cahyo; Basith Dir, Andi Akhmad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Laos located in The Greater Mekong Sub-Region (GMS). Because of its nature of crosscountry, Mekong River flows through Laos used as a gate of entry and exit of humantrafficking in Laos. Laos is a source country of human trafficking for women and children.Lao Women and Children are trafficked for sexual and labor exploitation. Furthermore,Laos is a transit country for victims trafficked from Vietnam to Thailand. Laos also is adestination country for women who are trafficked from Vietnam for sexual exploitation.Because of that, Laos cooperates with Vietnam for combating human trafficking containedin â€œAgreement between the Government of the Lao Peopleâ€™s Democratic Republic and theGovernment of the Socialist Republic of Vietnam on Cooperation in Preventing andCombating Trafficking in Personsâ€. The purpose of this study is to determine thecooperation is effective or not. Explanative type is use on this research to explain theeffectiveness of the agreement between the Government of the Lao Peopleâ€™s DemocraticRepublic and the Government of the Socialist Republic of Vietnam on cooperation incombating human trafficking in Laos. The result of this research shows that this agreementis not effective in combating human trafficking in Laos because there are other factors thattake effect in reduction of human trafficking in Laos.